2023
DOI: 10.3390/jpm13061014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Association of Burning Mouth Syndrome with Depressive and Anxiety Disorders in Middle-Aged and Older Adults: A Systematic Review

Abstract: Background: Burning Mouth Syndrome (BMS) is an idiopathic condition mainly affecting middle-aged and older individuals with hormonal disturbances or psychiatric disorders and is characterized by chronic pain. The etiopathogenesis of this multifactorial syndrome is largely unknown. The objective of the present systematic review was therefore to evaluate the relationship of BMS with depressive and anxiety disorders in middle-aged and older individuals. Methods: We selected studies evaluating BMS and depressive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A systematic review involving middle-aged and elderly subjects revealed a moderate association between BMS and anxiety disorder, but a lower correlation between BMS and depression disorder. 14 Women were shown to be at higher risk of developing BMS than men, and in addition to anxiety and depression, the study showed that personality characteristics, sleep disorders and bio-psychosocial changes worsened in middle-aged and elderly patients with BMS. 14 Because most of the results analysed by the researchers were from cross-sectional studies, the causal relationship between anxiety disorder, depressive disorder and BMS could not be determined.…”
Section: Negative Emotions and Oral Mucosal Diseasesmentioning
confidence: 91%
See 2 more Smart Citations
“…A systematic review involving middle-aged and elderly subjects revealed a moderate association between BMS and anxiety disorder, but a lower correlation between BMS and depression disorder. 14 Women were shown to be at higher risk of developing BMS than men, and in addition to anxiety and depression, the study showed that personality characteristics, sleep disorders and bio-psychosocial changes worsened in middle-aged and elderly patients with BMS. 14 Because most of the results analysed by the researchers were from cross-sectional studies, the causal relationship between anxiety disorder, depressive disorder and BMS could not be determined.…”
Section: Negative Emotions and Oral Mucosal Diseasesmentioning
confidence: 91%
“… 14 Women were shown to be at higher risk of developing BMS than men, and in addition to anxiety and depression, the study showed that personality characteristics, sleep disorders and bio-psychosocial changes worsened in middle-aged and elderly patients with BMS. 14 Because most of the results analysed by the researchers were from cross-sectional studies, the causal relationship between anxiety disorder, depressive disorder and BMS could not be determined. 14 Moreover, BMS is also frequently present in patients with Parkinson’s disease, characterized by dopamine dysregulation (confirmed by positron emission tomography) in the nigrostriatal dopaminergic pathway.…”
Section: Negative Emotions and Oral Mucosal Diseasesmentioning
confidence: 91%
See 1 more Smart Citation